STRATEGI KOMUNIKASI PUBLIC RELATIONS APARTEMEN REGATTA VB DALAM HANDLING COMPLAINT - Ita Suryani; Horidatul Bakiyah; Paryono Paryono (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
As a tenant relation who performs the role of public relations in an apartment certainly knows that building the trust of residents is one of the most important factors in achieving the success of managed apartments. And maintaining good relations with residents is one of the factors in how to be able to maintain tenants. The new apartment and management building has a huge potential for complaints from inside or outside. This has an impact on the emergence of residents' distrust regarding management's ability to manage building operations. The public relations communication strategy is expected to be able to bridge the relationship between the occupants and the building manager in building the residents' trust in order to create a harmonious relationship. The author uses qualitative-descriptive research methods conducted by interview and in-depth observation directly with related parties. The conclusion from the research carried out is that public relations communication strategy in two-way communication is very important, with a face-to-face model or through the media is important in relationship management. Two-way communication can be smooth, there is mutual understanding where the apartment management can consider the welfare of residents.